The Estimation of Biomass in Rhizophora apiculata and Rhizophora mucronata in Tuamese Village, North Central Timor Regency, East Nusa Tenggara Province - Ludgardis Ledheng; Yolanda Getrudis Naisumu; Remigius Binsasi (Jurnal Sylva Lestari, 2022)
Mangrove forest in North Central Timor Regency is dominated by Rhizophora sp. The highest number was found in Tuamese Village, namely Rhizophora apiculata and Rhizophora mucronata. The biomass productivity in mangrove forests varies according to age, dominant species, and locality. It shows differences in carbon uptake and storage at the level, type, and place of growth. This study aimed to analyze the carbon content and carbon uptake of R. apiculata and R. mucronata at the stake level to the tree level in two plots with the size of 2,000 m2 each. The method used was allometric equations, while the power discrimination test used an independent sample t-test. The result showed that R. apiculata and R. mucronata had the same potential in producing biomass and necromass as well as in storing and absorbing carbon. The total biomass was 77.21 Mg/ha, which can absorb and store carbon, respectively, 141.68 Mg/ha and 36.61 Mg/ha. This research data provides an overview of the potential of biomass in meeting carbon trading standards as an effort to succeed in mangrove conservation in Tuamese Village. Keywords: Biomass, Carbon uptake, Rhizophora apiculata, Rhizophora mucronata